2014
DOI: 10.1111/1758-2229.12217
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid substitution in homogentisate 1,2‐dioxygenase is responsible for pigmentation in a subset of Burkholderia cepacia complex isolates

Abstract: Summary The Burkholderia cepacia complex (Bcc) is a group of Gram-negative bacilli that are ubiquitous in the environment and have emerged over the past 30 years as opportunistic pathogens in immunocompromised populations, specifically individuals with cystic fibrosis (CF) and chronic granulomatous disease. This complex of at least 18 distinct species is phenotypically and genetically diverse. One phenotype observed in a subset of Burkholderia cenocepacia (a prominent Bcc pathogen) isolates is the ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…S3 in the supplemental material). Pyomelanin pigment, detected by absorbance at 480 nm ( 44 ), was significantly inhibited by CYS at concentrations above 8 μg/ml. The inhibition of these virulence determinants at sub-MICs may have further benefit therapeutically to enhance cotherapies and assist the innate and adaptive immune responses to infection.…”
Section: Resultsmentioning
confidence: 99%
“…S3 in the supplemental material). Pyomelanin pigment, detected by absorbance at 480 nm ( 44 ), was significantly inhibited by CYS at concentrations above 8 μg/ml. The inhibition of these virulence determinants at sub-MICs may have further benefit therapeutically to enhance cotherapies and assist the innate and adaptive immune responses to infection.…”
Section: Resultsmentioning
confidence: 99%
“…B. cenocepacia , especially strains from the ET12 lineage, are among the most prevalent Bcc members that colonize CF patients ( Isles et al, 1984 ; Speert et al, 2002 ; Mahenthiralingam et al, 2005 ; Drevinek and Mahenthiralingam, 2010 ). However, despite that many virulence factors were described, the epidemiological success of some lineages is still misunderstood ( Holden et al, 2009 ; McClean and Callaghan, 2009 ; Bazzini et al, 2011a ; Gonyar et al, 2015 ). The B. cenocepacia species is characterized by a large variety of ecological niches, from patient-associated to environmental niches.…”
Section: Discussionmentioning
confidence: 99%
“…cholerae 38 , A . salmonicida 37 , Legionella pneumophila 31 , Shewanella colwelliana 32 , Burkholderia cepacia 35 , B . cenocepacia 36 , Streptomyces avermitilis 34 , Ralstonia solanacearum 30 .…”
Section: Discussionunclassified
“…A search for this characteristic, i.e., higher pigmentation, in other bacteria showed that a subset of Burkholderia cepacia strains includes a deficient hmgA gene. In this case, rather than the truncation, the variant of the hmgA gene codes for a protein that has an amino acid substitution that is detrimental for enzymatic activity 35 .…”
Section: Discussionmentioning
confidence: 99%